BAD NEWS ANNOUNCEMENT ON INVESTORâS MONDAY IRRATIONALITY: INSIGHT FROM MALAYSIA - Brahmana, Rayenda; Hooy, Chee-Wooi; Ahmad, Zamri (Journal of Indonesian Economy and Business, 2012)
The lack of empirical dossiers on the examination of the weekend effect causesÂ intrigues us to investigate its determinant in the trading behaviour perspective. Employingone traditional interaction dummy model, and one day-by-day model, we found the marketÂ index and size-based portfolios of weekend effect have been driven by the attention ofÂ investor. Further, under the attention bias hypothesis, we confirm that investorâsÂ irrationality during Monday is the driver of the anomaly because of its heuristical biasÂ judgment. We address the difficulties that investors face on searching the thousands ofÂ stocks they can potentially deal on the first trading day as the rationalization. In a short,Â our findings surmise that attention bias is the driver of investor irrationality on MondayÂ and resulting Weekend Effect.Keywords: weekend anomaly, bad news, attention bias, Malaysia stock market